A critical analysis of anarchist critiques of the Field of “Solidarity and Cooperative Economy” in Greece - Gkagkelis Vaggelis (Social Change Review, 2021)
In this article, we explore the critiques developed by the anarchist social movement towards the “Solidarity and Cooperative Economy” in Greece. Initially, we outline the genealogy of the structural connection governing the “solidarity” economy with the development of contemporary social movements worldwide. Then, through the indexing of anarchist publications, we proceed to focus on two main anarchist critiques emphasizing on the economic and political problems of a “solidarity” economy which, in turn lead to the construction of the political position that refutes the interrelation of social movements with the field of alternative economy. We also outline the economic and political theory of classic anarchist thinkers: Kropotkin, Proudhon and Bakunin and we reappraise the critiques of the contemporary Greek anarchist movement based on these thinkers. Ultimately, the paper seeks to detect the points of convergence between the “Solidarity and Cooperative Economy” and contemporary anarchist movement. Deeming the practice of self-management as the principal interface between the anarchist thought and the organisation of networks and communities that constitute the “Solidarity and Cooperative Economy”, the present article calls for reflection and re-evaluation of these critiques with the ultimate objective being the delineation of new areas of political antagonism with capitalist structures and social change.